Relationship between ESG Scores and Fixed-Income Characteristics in Sustainable Funds - Suvorova, Kseniia (2025)
This thesis explores the relationship between ESG scores and fixed-income fund characteristics using a cross-sectional dataset of European bond funds classified under SFDR Articles 6, 8, and 9. The analysis evaluates whether Environmental, Social, and Governance dimensions are associated with risk-adjusted performance metrics, including Sharpe and Sortino ratios, volatility, downside risk, and interest rate sensitivity. Results show that Environmental scores are consistently linked to improved performance and lower risk, while Social and Governance dimensions offer limited explanatory value. These findings hold irrespective of SFDR classification, emphasizing the importance of disaggregated ESG metrics over formal sustainability labels in bond fund evaluation.